Experimental and Numerical Investigation for R/C Portal Frames Tested Under Uniform Load - Dheyaa Jaafar Witwit, Jaafar; Abed Al-Ameer Alwash, Nameer (International Journal of Engineering and Technology, 2018)
This paper presents an experimental and numerical investigations for three reinforced self-compacting concrete portal frames tested under uniform load. Control frame was tested without any types of strengthening, while second frame was strengthened with CFRP-sheet with dimensions (75 * 1000) mm at the bottom of beam and with dimensions (75 *700) mm at both joints, (350 mm) extending to the upper surface of the beam and (350 mm) on the outer face of the column. The last frame was cast in two pours tested without strengthening. The experimental tests showed that strengthened frame had stiffness more than control frame and its ultimate load was more than control frame by (19.45 %), while frame with two pours has an ultimate load less than a control frame with (11.26 %), however stiffness seem approximately to the control frame. Deflection for strengthened frame was less than control frame by (4.76%), on the other hand frame with two pours deflection was more than control frame by (4.55 %). A numerical finite element program ultimate load was more than experimental by about (4.28 %).Â Â